Liminal Metaphors and the Secularization of Roman Catholic Sisters - Miller, Ann (Anthropologica, 2022)
This paper examines one aspect of the interpretive process undertaken by religious communities of North American Roman Catholic sisters in the 1970s, or the redefinition of cloister. It is suggested that during this transitional period, widespread rejection of the concept of cloister as physical enclosure was more than a mere illustrative shift away from a communal paradigm stressing Utopian transcendence, and toward a communal paradigm identified as profane. In fact, this rejection signaled a transformation in the concept of cloister that allowed for continuity in communal themes of identity across contrasting paradigms. To effect this transformation, Roman Catholic sisters contrasted two liminal images: the transcendent Bride of Christ, and the profane clown.